A neoclassical perspective on Switzerland's 1990s stagnation - Yannic Stucki; Jacqueline Thomet (Swiss Journal of Economics and Statistics, 2021)
We study Switzerland's weak growth during the 1990s through the lens of the business cycle accounting framework of Chari et al. (Econometrica 75(3):781-836, 2007). Our main result is that weak productivity growth cannot account for the 1993-1996 stagnation episode. Rather, the stagnation is explained by factors that made labour and investment expensive. We show that increased labour income taxes and financial frictions are plausible causes. Holding these factors constant, the counterfactual annualized real output growth over the 1993Q1-1996Q4 period is 1.93% compared to realized growth of 0.35%.
Keywords: E13; E20; E32; E65; 330; Business cycle accounting; Housing crisis; Stagnation; Switzerland